Clustering Analysis of Life Expectancy at Birth in Central Sulawesi Province: Trends and Patterns 2022-2024 - Deni Luvi Jayanto; Prakasit Poonwong; Mohamed Fal Mohamed Fadel; Afiyah Rifkha Rahmika; Ni’matu Zuliana; Mia Ashari Kurniasari; Ayu Hernita (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Life Expectancy at Birth (LEB) is a critical indicator of health and well-being, and understanding its variations across regions is essential for effective health policy development. In Central Sulawesi, Indonesia, LEB has shown improvements over recent years. This study aims to explore life expectancy trends in Central Sulawesi from 2022 to 2024 using K-means clustering analysis. The study uses secondary data from the Central Statistics Agency (BPS), focusing on health indicators, education levels, healthcare access, and socio-economic conditions. The results revealed that most districts in Central Sulawesi fall into the high life expectancy category (C3), including urban areas like Palu and Morowali, reflecting better healthcare infrastructure and socio-economic conditions. However, districts such as Parigi Moutong, Tojo Una-Una, and Banggai Kepulauan remain in the lower life expectancy categories (C1 and C2), highlighting significant disparities. These findings underscore the need for targeted interventions to address the healthcare and socio-economic challenges in lower-performing areas. The study concludes that while Central Sulawesi has made progress in improving life expectancy, regional disparities remain. Policymakers should focus on enhancing healthcare access, infrastructure, and education in underdeveloped areas to reduce these gaps on addressing the challenges faced by districts in the C1 and C2 categories.